Effectiveness Of Using GIS Technologies In Agriculture (Czech Journal of Multidisciplinary Innovations, 2024)
Nowadays, the use of GIS technologies is relevant. Therefore, there is a need to justify the advantages of GIS technologies. This article describes the effectiveness of the use of GIS technology in the agricultural sector.